Exploring and Comparing Cognitive Moral Reasoning of Millennials and Across Multiple Generations. (26th September 2018) - Weber, James; Elm, Dawn R.
Abstract: This research builds on previous investigations seeking to understand how individuals reason about moral problems. Our research includes a preliminary investigation about Millennials and a cross‐generational analysis using secondary research data to understand this emerging generation's moral reasoning and assess trends in moral reasoning over time. This study addresses content‐bias in moral reasoning by using a new instrument with business‐based dilemmas, the Moral Recognition Interview, based on the well‐established moral reasoning framework of Lawrence Kohlberg. Results show that the Millennials in this study exhibit differences in moral reasoning based on gender, intelligence, work experience, and academic major, however not necessarily in an expected manner. Differences in moral reasoning were found when the context or "story pull" of the ethical dilemmas presented is considered. In addition, a comparison to other studies shows that business student Millennials tend to reason at lower levels of cognitive moral reasoning than non‐business college students, as well as college students in the 1960s–1970s (Baby Boomers) and in the 1980s–1990s (Generation Xers).